Flow cytometry for the analysis of α-dystroglycan glycosylation in fibroblasts from patients with dystroglycanopathies. - Elizabeth Stevens; Silvia Torelli; Lucy Feng; Rahul Phadke; Maggie C Walter; Peter Schneiderat; Ayad Eddaoudi; Caroline A Sewry; Francesco Muntoni (PLoS ONE)
α-dystroglycan (α-DG) is a peripheral membrane protein that is an integral component of the dystrophin-glycoprotein complex. In an inherited subset of muscular dystrophies known as dystroglycanopathies, α-DG has reduced glycosylation which results in lower affinity binding to several extracellular matrix proteins including laminins. The glycosylation status of α-DG is normally assessed by the binding of the α-DG antibody IIH6 to a specific glycan epitope on α-DG involved in laminin binding. Immunocytochemistry and immunoblotting are two of the most widely used methods to detect the amount of α-DG glycosylation in muscle. While the interpretation of the presence or absence of the epitope on muscle using these techniques is straightforward, the assessment of a mild defect can be challenging. In this study, flow cytometry was used to compare the amount of IIH6-reactive glycans in fibroblasts from dystroglycanopathy patients with defects in genes known to cause α-DG hypoglycosylation to the amount in fibroblasts from healthy and pathological control subjects. A total of twenty one dystroglycanopathy patient fibroblasts were assessed, as well as fibroblasts from three healthy controls and seven pathological controls. Control fibroblasts have clearly detectable amounts of IIH6-reactive glycans, and there is a significant difference in the amount of this glycosylation, as measured by the mean fluorescence intensity of an antibody recognising the epitope and the percentage of cells positive for the epitope, between these controls and dystroglycanopathy patient fibroblasts (p<0.0001 for both). Our results indicate that the amount of α-DG glycosylation in patient fibroblasts is comparable to that in patient skeletal muscle. This method could complement existing immunohistochemical assays in skeletal muscle as it is quantitative and simple to perform, and could be used when a muscle biopsy is not available. This test could also be used to assess the pathogenicity of variants of unknown significance in genes involved in dystroglycanopathies.